Management of Pathological Thoracolumbar Vertebral Fractures in Patients With Multiple Myeloma: Multidisciplinary Recommendations. Issue 1 (April 2023) - Osterhoff, Georg; Kreinest, Michael; Kuhnt, Thomas; Pohlenz, Claudia; Müller-Broich, Jacques; Röllig, Christoph; Teipel, Raphael; Scheyerer, Max J.; Schnake, Klaus John; Spiegl, Ulrich J. A.; Disch, Alexander C.; ,
Study Design: Mutlidisciplinary consensus recommendations for patients suffering from multiple myeloma (MM) involvement of the spinal column by the Spine Section of the German Association of Orthopaedic and Trauma Surgeons. Objective: To provide a comprehensive multidisciplinary diagnostic and therapeutic approach and to summarize the current literature on the management of pathological thoracolumbar vertebral fractures in patients with multiple myeloma. Methods: Multidisciplinary recommendations using a classical consensus process provided by radiation oncologists, medical oncologists, orthopaedic- and trauma surgeons. A narrative literature review of the current diagnostic and treatment strategies was conducted. Results: Treatment decision has to be driven by a multidisciplinary team of oncologists, radiotherapists and spine surgeons. When considering surgery in MM patients, differing factors compared to other secondary spinal lesions have to be included into the decision process: probable neurological deterioration, the stage of the disease and prognosis, patient's general condition, localization and number of the lesions as well as patient's own wishes or expectations. Aiming to improve quality of life, the major goal of surgical treatment is to preserve mobility by reducing pain, secure neurological function and stability. Conclusion: The goal of surgery is primarily to improve quality of life by restoring stability and neurological function. Interventions with an increased risk of complications due to MM-associated immunodeficiency must be avoided whenever feasible to allow early systemic treatment. Hence, treatment decisions should be based on a multidisciplinary team that considers patient's constitution and prognosis.